Power emblems in San Pedro de Atacama during the Middle Period (400-1.000 A.D.): The case of axes and metal maces - Cifuentes Aguilar, Ariadna (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2020)
Metals recorded in the burials of the cemeteries of San Pedro de Atacama had a significant increase during the Middle Period. They would have played an important role in setting sociopolitical relationships between local leaders and other relevant political entities of the time, such as Tiwanaku or Aguada. This research discusses the case of axes and metal maces, objects that had a limited but recurrent distribution in Atacameño cemeteries of the time. In addition, these objects might imply political power of their owners, acting as power emblems of local leaders. Based on the results, issues related to circulation and consumption of this type of objects are discussed in the context of the Middle Period in San Pedro de Atacama.